Complementary foods in infants: an in vitro study of the faecal microbial composition and organic acid production - Geniselli da Silva V; Mullaney JA; Roy NC; Smith NW; Wall C; Tatton CJ; McNabb WC (Royal Society of Chemistry, 2025)
The transition from breastmilk to complementary foods is critical for maturing the colonic microbiota of infants. Dietary choices at weaning can lead to long-lasting microbial changes, potentially influencing health later in life. However, the weaning phase remains underexplored in colonic microbiome research, and the current understanding of how complementary foods impact the infant's colonic microbiota is limited. To address this knowledge gap, this study assessed the influence of 13 food ingredients on the in vitro microbial composition and production of organic acids by the faecal microbiota in New Zealand infants aged 5 to 11 months. To better represent real feeding practices, ingredients were combined with infant formula, other complementary foods, or both infant formula and other foods. Among the individual food ingredients, fermentation with peeled kūmara (sweet potato) increased the production of lactate and the relative abundance of the genus Enterococcus. Fermentation with blackcurrants, strawberries, or raspberries enhanced acetate and propionate production. Additionally, fermentation with blackcurrants increased the relative abundance of the genus Parabacteroides, while raspberry fermentation increased the relative abundance of the genera Parabacteroides and Eubacterium. When combined with infant formula or with blackcurrants, fermenting black beans increased butyrate production and stimulated the relative abundance of Clostridium sensu stricto 1. These foods are promising candidates for future clinical trials.